Melindungi Kreativitas di Tanah Air: Lanskap Hukum Hak Cipta Indonesia di Tengah Disrupsi Teknologi - Nazar Junio; Romi Faslah (GLOBAL SCIENTS PUBLISHER, 2025)
This article analyzes the landscape of Indonesian copyright law amidst technological disruption. The creative economy significantly contributes to Indonesia's GDP, making robust copyright protection essential. However, rapid technological advancements, particularly digitalization and Artificial Intelligence (AI), pose complex challenges to the existing legal framework, primarily Law No. 28 of 2014 concerning Copyright (UUHC) and Law No. 11 of 2008 concerning Information and Electronic Transactions (UU ITE). This research employs a normative juridical approach with qualitative analysis of secondary data to evaluate the effectiveness of current regulations, identify the impacts of disruptive technologies like AI and blockchain, assess law enforcement efforts by the Directorate General of Intellectual Property (DJKI), and formulate recommendations. Key findings indicate that the current legal framework is not fully adequate to address AI-related issues such as authorship and originality, and digital piracy remains rampant despite enforcement efforts. The study concludes that comprehensive legal reforms, institutional strengthening, leveraging technology for protection, and enhancing public awareness are crucial for safeguarding creativity in Indonesia's evolving digital era. Recommendations include revising the UUHC to address AI, enhancing DJKI's capacity, exploring an Internet Court, utilizing blockchain for rights management, and intensifying public education.